If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7x + -8)(3x + 2) = 0 Reorder the terms: (-8 + 7x)(3x + 2) = 0 Reorder the terms: (-8 + 7x)(2 + 3x) = 0 Multiply (-8 + 7x) * (2 + 3x) (-8(2 + 3x) + 7x * (2 + 3x)) = 0 ((2 * -8 + 3x * -8) + 7x * (2 + 3x)) = 0 ((-16 + -24x) + 7x * (2 + 3x)) = 0 (-16 + -24x + (2 * 7x + 3x * 7x)) = 0 (-16 + -24x + (14x + 21x2)) = 0 Combine like terms: -24x + 14x = -10x (-16 + -10x + 21x2) = 0 Solving -16 + -10x + 21x2 = 0 Solving for variable 'x'. Factor a trinomial. (-2 + -3x)(8 + -7x) = 0Subproblem 1
Set the factor '(-2 + -3x)' equal to zero and attempt to solve: Simplifying -2 + -3x = 0 Solving -2 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -3x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -3x = 0 + 2 -3x = 0 + 2 Combine like terms: 0 + 2 = 2 -3x = 2 Divide each side by '-3'. x = -0.6666666667 Simplifying x = -0.6666666667Subproblem 2
Set the factor '(8 + -7x)' equal to zero and attempt to solve: Simplifying 8 + -7x = 0 Solving 8 + -7x = 0 Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -7x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -7x = 0 + -8 -7x = 0 + -8 Combine like terms: 0 + -8 = -8 -7x = -8 Divide each side by '-7'. x = 1.142857143 Simplifying x = 1.142857143Solution
x = {-0.6666666667, 1.142857143}
| -3(5x-11)=138 | | 7(2x+3)-12x=3x+17 | | -8n=32 | | 0.15x+0.05(20-x)=0.10(22) | | 2x^2-5x+3=3 | | 0.80x+20.00=100 | | 2(10m-7a)+3(8a-3m)= | | 7(3x+4+2x)=63 | | 0.80x+20.00=281.60 | | y=-9/7x+2 | | x+14=29 | | 0=-100+(.7q-6)q | | 2(22-3*7)= | | 28-16=3(x-1) | | b+a=cx | | 2(x+6)=12+2x | | ln(2x^4+10x^3)+ln(1/(3x^3)) | | 7-6=12-2x | | 0=cx-a+b | | cx-a+b=2b | | 5x+-10=21-6x | | 9+x/2=10 | | 1x-4y=-27 | | y=5sinx+3x | | -4x/3=12 | | 355-5x=0+5x | | -3/4y+2=14 | | -2(3n-1)-n=5(n-4) | | 6/5+x=4/7 | | 120+10x=15+4x | | 2x+(2*2*x+5)=949 | | x-52=194 |